TEACHING THE SELF-SUSTAINING ABILITY IN SWIMMING LESSONS (Fiep Bulletin - online, 2013)
The ability of self-sustaining in the water may Represent the limits between knowing and not knowing how to swim because keeping yourself in the water without any auxiliary support would be vital for the swimmer where the bottom Could not be reached. This study investigated the teaching of self-sustaining in the water at swimming Institutions that offer swimming lessons and have only shallow pools. 13 teachers from 09 educational Institutions were interviewed swimming in the city of Blumenau. Swimming lessons are almost Given Exclusively in shallow pools and the fact That's not the Institutions have deep pools, Contributes to the Lack of self-sustaining skills who Reaches to the bottom, covering only children. We recommend the realization of studies to investigate strategies of teaching self-sustaining in shallow pools providing safety to the students in the bottom situations where they could not be reached.
Keywords: Education; Swimming; self-sustaining.